Hospital utilization for patients with amyotrophic lateral sclerosis in saskatoon, Canada. Issue 3 (3rd April 2018) - Gunton, Adrianna; Hansen, Gregory; Schellenberg, Kerri Lynn
Abstract: Objective: This retrospective study reviewed hospital and intensive care unit (ICU) admissions for patients with amyotrophic lateral sclerosis (ALS) in Saskatoon, Canada, between 2005 and 2017. The purpose was to understand hospital utilization and admission patterns for patients with ALS in the absence of coordinated multidisciplinary care. Methods: Hospital/ICU admissions were detected at two hospitals in Saskatoon using the International Classification of Diseases (ICD-10) coding for ALS. Patient demographic data, hospitalization and pre-hospitalization information were recorded, and descriptive statistics were generated. Results: Of the 83 patients identified, 52% were male with a mean age of 66.8 years. Fifty-two percent were undiagnosed prior to hospitalization, with significantly longer ICU stays compared to those diagnosed prior to admission (49.4 ± 46.6 vs. 21.9 ± 32.0 days; p  = 0.0003). Eighty-nine percent of all admissions ( n  = 118) were non-elective. Although respiratory dysfunction was the most common reason for admission ( n  = 41, 49%), and all ICU admissions were for respiratory dysfunction, only 2% were on non-invasive ventilation prior to ICU admission. All tracheostomies ( n  =10, 12%) were placed non-electively, and 50% were in previously undiagnosed patients. Thirty-four percent ( n  = 28) of patients died in hospital in an ICU ( n  = 8, 29%) and hospital wards ( n  = 20, 71%). Conclusion: ALS patients in Saskatoon had high non-elective admission rates, with over half undiagnosed prior to hospitalization, and high rates of emergent tracheostomy. This study highlights the need for early diagnosis and coordinated multidisciplinary care for improved outpatient management of ALS to reduce lengthy and complicated hospitalizations.